Design and Construction of a Thermopile. - Bogere, Sula (Kabale University, 2024)
This project aimed to design and construct a thermopile detector. It was guided by the following objectives; to design and construct a thermopile; to enhance teaching and to ease learning process for the learners, and to acquire skills in improvising teaching aids in the teaching process